Analysis of economic growth and unemployment in South Sulawesi - Musyawarah Musyawarah (Indonesia Accounting Research Journal, 2022)
The purpose of this research is to find out whether the interest rate and inflation rate affect unemployment and economic growth in South Sulawesi province. The analytical method used is multiple regression analysis. The results of this study indicate that the interest rate variable has a negative and significant effect on economic growth, and the inflation variable has a negative and insignificant effect on economic growth, while unemployment has a negative and significant effect on economic growth, while the inflation rate has a negative and insignificant effect on unemployment, and economic growth has a negative and significant effect on unemployment.